The caves of Qumran : proceedings of the international conference, Lugano 2014 - Fidanzio, Marcello. (Studies on the Texts of the Desert of Judah, 2016)
In Qumran studies, the attention of scholars has largely been focused on the Dead Sea Scrolls, while archaeology has concentrated above all on the settlement. This volume presents the proceedings of an international conference (Lugano 2014) dedicated entirely to the caves of Qumran. The papers deal with both archaeological and textual issues, comparing the caves in the vicinity of Qumran between themselves and their contents with the other finds in the Dead Sea region. The relationships between the caves and the settlement of Qumran are re-examined and their connections with the regional context are investigated. The original inventory of the materials excavated from the caves by Roland de Vaux is published for the first time in appendix to the volume.